2014
DOI: 10.1089/met.2013.0038
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Short-Term Cardiac Rehabilitation After Acute Myocardial Infarction on High-Sensitivity C-Reactive Protein

Abstract: Our study revealed that hsCRP and metabolic syndrome parameters can be substantially reduced by a 2-week CR program; however, this effect is present only in nonsmokers. Thus, all patients entering the CR program after AMI should be advised to quit smoking before entering the program to achieve optimal benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
1
0
2
Order By: Relevance
“…reported that a four-week CR program could significantly reduce hs-CRP levels among STEMI patients, from 3.1 mg/L to 2.1 mg/L ( P < 0.0001) [13]. In 2014, a study conducted in Slovenia found that patients with acute MI had higher baseline levels of hs-CRP than healthy individuals; while, after a 2-week CR was applied, hs-CRP significantly diminished in the non-smokers ( P < 0.006), but not among the smoker patients [14]. A recent study in Romania showed that CR is as much effective as statins in reducing the hs-CRP levels among acute MI patients [15].…”
Section: Discussionmentioning
confidence: 99%
“…reported that a four-week CR program could significantly reduce hs-CRP levels among STEMI patients, from 3.1 mg/L to 2.1 mg/L ( P < 0.0001) [13]. In 2014, a study conducted in Slovenia found that patients with acute MI had higher baseline levels of hs-CRP than healthy individuals; while, after a 2-week CR was applied, hs-CRP significantly diminished in the non-smokers ( P < 0.006), but not among the smoker patients [14]. A recent study in Romania showed that CR is as much effective as statins in reducing the hs-CRP levels among acute MI patients [15].…”
Section: Discussionmentioning
confidence: 99%
“…Nuestros pacientes tuvieron una tasa má s alta de abstinencia de tabaco que en estudios previos independientemente del grupo asignado. Esto es muy relevante, ya que los beneficios de muchos tratamientos podrían reducirse o incluso quedar suprimidos en los fumadores persistentes 13,14 .…”
Section: Discusió Nunclassified
“…realizar PRC adaptados a estos pacientes. En esta línea, algunos estudios que evaluaron la conveniencia de PRC de 2 semanas de duració n mostraron solo una mejora de la capacidad de ejercicio y variables sustitutivas, como el estré s oxidativo o marcadores inflamatorios, aunque sin comparar directamente sus resultados con los de programas tradicionales de mayor duració n [13][14][15] .…”
Section: Introduccionunclassified